Perinatal outcomes of African refugees after their integration into the Israeli health care system. (August 2020) - Gil, Yaron; Lavie, Michael; Balayla, Jacques; Toledano, Ella; Michaan, Nadav
Abstract: Objective: Evaluate whether the incorporation of the refugees into the Israeli medical system resulted in improvements in perinatal outcomes, namely a reduction in the number of preterm deliveries and a decrease in NICU admissions. Methods: Retrospective cohort study. Electronic medical records of all African immigrants who delivered in our tertiary referral center between January 2018 and September 2019 were reviewed. African patients' demographics, maternal and perinatal outcomes were compared to those of native Israeli population. In addition, the results were compared to the cohort from our previous study from 2010. Results: A total of 20, 796 deliveries took place at our labor and delivery department during the study period. Of these, 3% of all deliveries were of African refugees. Total rates of preterm deliveries <37 weeks was similar between groups, while rate of premature deliveries <34 week was higher among refugees. Rates of extreme prematurity <28 weeks were also similar between groups. Rate of meconium stained amniotic fluid, neonatal weight <2000 g as well as NICU admissions were significantly higher among refugees. Conclusion: Though perinatal results have not substantially improved with the incorporation of a refugee population into a healthcare system, some progression has indeed been achieved in some perinatal parameters.